2003
DOI: 10.1093/fampra/20.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Identification of patients attending Accident and Emergency who may be suitable for treatment by a pharmacist

Abstract: A pharmacist could manage an estimated 8% of adult attendances at this A&E department. Efforts should be made to increase the awareness of the general public of the role of a community pharmacist to reduce demand on A&E and GP services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…It depends on the definition and of the contextual factors, if consultations are estimated as “Minor Ailments”. In the available literature the percentage of minor ailments varies from 8 to 40% [15, 17, 2933]. …”
Section: Discussionmentioning
confidence: 99%
“…It depends on the definition and of the contextual factors, if consultations are estimated as “Minor Ailments”. In the available literature the percentage of minor ailments varies from 8 to 40% [15, 17, 2933]. …”
Section: Discussionmentioning
confidence: 99%
“…However, 42% of those could have also been handled by a community pharmacist. 4 Hammond et al found that GPs felt that 7% of their cases could have been handled by a community pharmacist. 5 Therefore, primary health care would greatly benefit from a low-threshold entry into the health care system, as offered by telemedicine or pharmacies, where efficient primary triage would then treat or dispatch patients to the appropriated setting according to the severity and urgency of the cases.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Up to 18% of general practice workload is estimated to relate to minor ailments, at a cost of £2 billion annually. 6 Similarly, 8% of emergency department consultations involve consultations each year for minor ailments, 7 costing the NHS £136 million annually. Research shows that GPs are in favour of diverting the care of minor ailments to other areas of primary care, including community pharmacists.…”
Section: Introductionmentioning
confidence: 99%